Firm Performance in the Telecommunication Sector: Empirical Evidence on the Interplay of Corporate Social Responsibility and Employee Engagement - La`aleh Al-Aali, Mohammed Ali Aour, Mahmoud Radwan Hussein AlZgool (International Journal of Advanced Science and Technology, 2020)
Performance is the ultimate goal of every business entity. Therein, the evolving business dynamics always keep the question of managing and improving performance alive. The current study attempted to investigate how firm performance could be enhanced. Therein, the study worked to test how socially responsible initiatives of an organization can help enhance the firm performance followed by the role of employee engagement. Questionnaire technique was used to collect data from managerial and supervisory level employees in three major telecommunication companies in Bahrain. Results from the PLS path modelling approach reported significant relationship between firm`s corporate social responsibility activities and performance hence suggesting that socially responsible behaviour and initiatives can yield better firm performance results. The study also reported significant positive relationship between employee engagement and firm performance which asserts that organizations need to work on developing measures and prospects to further employee engagement for better company results. However, the study failed to find any significant moderation of employee engagement on the CSR-firm performance relationship. The study forwards notable implications for theory and practice followed by limitations and scope for future scholars.